Diversity, equity, and inclusive education a voice from the margins - Gause, C. P.; SpringerLink (Online service). (Rotterdam SensePublishers, 2011)
The United States is more ideologically, philosophically, culturally, linguistically, racially, and ethnically diverse than she has been in any given point in her history; however, many of her citizens are currently living in a state of fear. What stands out the most is how we allow this fear to take over our lives in multiple ways. We fear our neighbors; therefore, we do not engage them. We fear young people and the way they look; therefore, we do not have conversations with them. We fear the possibility of terrorists attacks; therefore, we utilize eavesdropping and surveillance devices on our citizens. There are some of us who fear the lost of gun rights; therefore, we stockpile weapons. We fear anything that is different from who we are and what we believe. This nation has, at many points within our history, become more united because of our fear; however, as our borders, physical and virtual, become less protective and the opportunities to connect more via the digital world expand, we must educate our citizenry to not live in fear but in hope. To teach, learn, and lead democratically requires the individual to engage in problem posing and in critiquing taken-for-granted narratives of power and privilege. Critical change occurs with significant self-sacrifice, potential alienation/rejection, and costly consequences. Educators must do justice to the larger social, public, and institutional responsibility of our positions, and we must exercise courage in creating opportunities for change. Diversity, Equity, and Inclusive Education: A Voice from the Margins, provides the space and opportunity to move beyond a state of fear, into a state of organic transformation, a place where fear creates the energy to speak those things that are not, as though they were.
Electronic reproduction.
Keywords: Educational equalization -- United States; Progressive education -- United States; Electronic books